Life Themes and Attachment System in the Narrative Self-Construction: Direct and Indirect Indicators - Di Fini, Giulia; Veglia, Fabio (Frontiers in Psychology, 2019)
The narration is the instrument that allows individual to organize his experience through a process of attribution and sharing of meaning within social interactions and to translate the extraordinary in normativity. As regards the narrative content there are "narrative genres" that impose thematic constraints on the way of narrating, but these also allow creative variations. According to the theoretical-clinical hypothesis of Life Themes (LTs), Love, Value, Power, Freedom, and Truth are shared attractors of meaning recurring in Life Stories. The influence of attachment system on the development of autobiographical narratives is shown in literature. This article presents a qualitative study of the specific dimensions and valences of the LTs in the adult attachment narratives. The study is part of a broader research project that aims to systematize the theoretical model of LTs in the narrative Self-construction, to study its connections and applications in the field of attachment theory, and to build a useful operative tool in the clinical assessment of patients’ stories. We also aimed to study the occurrence of the LTs in the Adult Attachment Interview transcripts, preliminarily exploring possible connections with Internal Working Models. 40 AAI transcripts of 20 men and 20 women (mean age was 33 years old), selected from a larger non-clinical sample employed in an adult attachment study, were analysed using a phenomenological exploratory approach. For the research design we used a qualitative methodology that ensure a deep and intensive, rather than extensive, analysis, focusing on the complexity of meanings and discussing the results within the research group. Several indicators of LTs have been identified and the interpersonal dimensions were explored. An additional Theme emerged from the recurrence of some indicators: Ethic and Justice. In Dismissing subjects' narrations the theme Value (in terms of being valued) emerges mostly, while in the Preoccupied ones the theme Power (in terms of impositions received), accompanied secondarily by Value and Freedom, occurs more frequently. The most frequent thematic indicators in the F group are related to Love and Truth. Clinical implications of an explicative model of critical Themes are discussed.